Designing a peer-led approach to teaching review and enhancement in academia - Moritz, Dominique; Pearce, Simone; Christensen, Larissa; Stamboulakis, Drossos (Journal of University Teaching and Learning Practice, 2021)
One of the challenges of 21st-century academia is meeting the often-competing demands from students, universities, and professional associations. Among many diversities, students at regional universities, such as the University of the Sunshine Coast (USC), often have higher rates of first-in-family learners than metropolitan counterparts. Law academics at regional universities, then, must address the challenges of maintaining high-quality teaching to fulfil student satisfaction for a diverse student demographic, while both meeting university and professional requirements and supporting students’ personal satisfaction. One avenue to support academics in enhancing teaching practices while aligning with university and professional obligations is through peer discussion, review, and enhancement of learning and teaching practice. Peer discussion, enhancement, and review of learning and teaching practice occurs regularly on an informal basis in most academic settings. However, opportunities to engage in structured and meaningful peer review and enhancement of teaching are neither prevalent nor popular. Academic staff in the School of Law and Criminology (SLC) at USC instigated and developed an interdisciplinary, formalised framework for enhancing teaching and learning practice within the SLC, in accordance with the SLC’s mission: to provide a personal, inspiring, and rigorous learning environment that empowers graduates to be career- and future-ready and able to make significant contributions to their communities. This framework, termed Peer Review and Enhancement of Practice (PREP), delivers a teaching-enhancement best-practice structure that is informed by evidence-based pedagogy and involves shared experience, self-reflection, and peer review. PREP is innovative in nature through its ground-up approach, which is driven by academic staff within the SLC, to create a collaborative space that is relevant and suitable for academic staff to address learning and teaching challenges and opportunities. Accordingly, PREP is flexible, voluntary, and organic, tailored to suit the needs and wants of academic staff. PREP also provides an opportunity for academic staff to develop portfolios that collate authentic evidence of effective learning and teaching